2022
DOI: 10.3389/fgene.2022.913908
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms and Kidney Stones Around the Globe: A Systematic Review and Meta-Analysis

Abstract: Objective: This study explores associations between recurrent kidney stones and genetic polymorphisms.Methods: Meta-analysis of polymorphisms in renal stone cases versus control groups. Four electronic databases (PubMed, SCOPUS, EMBASE, and Web of Science) were searched up to 30 May 2021, using the keywords: “kidney stone” or “kidney calculi,” or “urolithiasis” or “nephrolithiasis” or “urinary calculi” and “genome” or “genetic” or “mutation” or “single nucleotide polymorphism.” Forrest plots, ORs, 95% CI, Chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Klotho gene G395A single-nucleotide polymorphisms were linked to the formation of renal stones among North Indian patients with KS [ 28 ]. Moreover, a meta-analysis involving five distinct research studies revealed that Klotho prevented the development of urinary stones [ 20 ]. All studies were conducted in Asian countries, and only a small number focused on the US population, which lessens their external validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klotho gene G395A single-nucleotide polymorphisms were linked to the formation of renal stones among North Indian patients with KS [ 28 ]. Moreover, a meta-analysis involving five distinct research studies revealed that Klotho prevented the development of urinary stones [ 20 ]. All studies were conducted in Asian countries, and only a small number focused on the US population, which lessens their external validity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vitro CaOx KS model, Klotho overexpression prevented the CaOx-induced enhancement of crystal cell adhesion and apoptosis in HKC cells, whereas in vivo assays revealed that Klotho overexpression reduced renal oxidative injury, renal apoptosis, and crystal deposition that were caused by glyoxylate administration in mouse kidneys [ 18 ]. The Klotho gene demonstrated a protective effect, with multiple studies demonstrating a strong correlation between Klotho gene variations and urolithiasis susceptibility [ 19 , 20 ]. However, most studies on the relationships between Klotho gene polymorphisms and KS were conducted in Asia and lacked information on multiethnicity, which might be considered a confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…Published data reported a negative correlation between seminal methylation status of CGI2, located in the VDR promoter region, and both sperm concentration and progressive motility, strengthening the potential role of this epigenetic mechanism in male infertility [39]. Methylation of VDR has also recently been investigated in the pathological state of recurrent kidney stone formation, given the significant association between the genetic variability of VDR and urinary stone formation risk [40,72]. In the study from Khatami et al, VDR methylation analysis was performed in 30 consecutive recurrent kidney stone formers and 30 age and gender-matched CTRs, revealing a hypermethylation pattern of two VDR promoter regions, including 5 and 11 CpG sites, in cases respect to CTRs [40].…”
Section: Other Diseasesmentioning
confidence: 99%
“…Published data reported a negative correlation between the seminal methylation status of CGI2, located in the VDR promoter region, and both sperm concentration and progressive motility, strengthening the potential role of this epigenetic mechanism in male infertility [ 42 ] ( Figure 2 ). The methylation of the VDR has also recently been investigated in the pathological state of recurrent kidney stone formation, given the significant association between the genetic variability of VDR and urinary stone formation risks [ 43 , 75 ] ( Table 1 ). In the study conducted by Khatami et al VDR methylation analysis was performed in 30 consecutive recurrent kidney stone formers and 30 age and gender-matched CTRs, revealing a hypermethylation pattern of two VDR promoter regions, including 5 and 11 CpG sites, in cases related to CTRs [ 43 ] ( Figure 2 ).…”
Section: Other Diseasesmentioning
confidence: 99%